2012
DOI: 10.1007/s13594-012-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Norwegian autochthonous cheese Gamalost and its angiotensin I-converting enzyme (ACE) inhibitory activity during ripening

Abstract: 19Gamalost, a mould-ripened semi-hard traditional Norwegian cheese, has previously

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 15 publications
1
27
1
1
Order By: Relevance
“…Usually, the formation of BA in cheese increase during ripening (Kebary et al 1999;Ordóñez et al 1997) but in Gamalost the development of putrescine did not increase further during ripening beyond 10 days until 30 days even though the content of the precursors of putrescine, i.e. arginine and glutamine increased during ripening in our previous study (Qureshi et al 2012a). After 30 days, the content of putrescine seemed to be decreased in the Gamalost, but as the standard deviation at 60 days was very high, that decrease seemed to be batch dependent.…”
Section: Biogenic Aminesmentioning
confidence: 60%
See 4 more Smart Citations
“…Usually, the formation of BA in cheese increase during ripening (Kebary et al 1999;Ordóñez et al 1997) but in Gamalost the development of putrescine did not increase further during ripening beyond 10 days until 30 days even though the content of the precursors of putrescine, i.e. arginine and glutamine increased during ripening in our previous study (Qureshi et al 2012a). After 30 days, the content of putrescine seemed to be decreased in the Gamalost, but as the standard deviation at 60 days was very high, that decrease seemed to be batch dependent.…”
Section: Biogenic Aminesmentioning
confidence: 60%
“…Stratton et al (1991) reported that consumption of ripened cheese with high contents of BA may pose a risk on public health and histamine poisoning has been reported from Gouda, Swiss, Cheddar, Cheshire, Gruyere (Stratton et al 1991). The proteolysis of Gamalost is substantial and the content of free amino acids in this cheese is rather high as compared to other cheeses (Qureshi et al 2012a). The ripening of Gamalost is caused by a Mucor mould, which makes the ripening of Gamalost completely different from other cheeses, and the contribution of this mould to the production of menaquinones (MK) is unknown.…”
mentioning
confidence: 84%
See 3 more Smart Citations